メキシコ・シティの都市民衆ネットワークとコミュニティ開発 - 天野 裕; 吉田 祐記; 土肥 真人; 木村 直紀 (住宅総合研究財団研究論文集, 2011)
This study focuses on Programa Comunitario de Mejoramiento Barrial (PCMB), a community-based program that runs a comprehensive set of cultural, health, environmental, educational and employment projects within a low-income neighbourhood in Mexico City. Researches were conducted with 4 cases which are adopted by PCMB in 2007, regarding relationship between the grass-roots movements prior to the adoption and the PCMB process in each case. In conclusion, 1) the PCMB program contributes to improving public space and infrastructure, meeting local needs flexibly; 2) the PCMB program works more effectively with prior grass-roots movement. 本研究は，メキシコ・シティの地区改良コミュニティプログラム（PCMB）を対象とし，2007年度採択プログラム45件から，参加の程度，独創性，達成度が高い地区を４件抽出し，各地区の都市民衆運動およびそれに準ずる活動の前史とPCMBの実施プロセス，実施後の展開との関係性について調査を行った。結論として，PCMBが地区の実情に応じて様々な公共空間整備に寄与していること，従前の住環境改善の組織的取り組みがＰＣＭＢ実施の効果を高めていることを明らかにした。また，PCMB実施上の指針として，1.制度的資源の活用，2.地域的資源の開拓，3.地域アイデンティティの醸成，4.手法の明文化・継承の4点を提示した。